Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

The Sandbox Model: A Novel Approach to Iterating while Implementing an Emergency Education Program in Lebanon during the COVID-19 Pandemic - Boujikian, Michèle; Carter, Alice; Jordan, Katy (2022)
Jusoor’s Refugee Education Program helps Syrian refugee children living in Lebanon integrate back into formal schooling. When schools closed due to the COVID-19 pandemic, the refugee program adapted to distance learning by developing Azima, a novel program that used WhatsApp to enable children to keep learning. Azima had to respond immediately to the emergency context while maintaining high education standards, and it also needed to find an effective way to test and refine its content quickly. To do this, the Azima program adopted an innovative experimental approach called a sandbox. A sandbox model operates in rapid iterative cycles and uses multiple methods to quickly test a program’s assumptions about how it will meet its goals. In this field note, we use Azima as a case study to report on our experience of applying the sandbox model. We reflect on the benefits and limitations of this novel approach in supporting the use of education technology in a crisis situation.

Is there Learning Continuity during the COVID-19 Pandemic? A Synthesis of the Emerging Evidence - McBurnie, Chris; Adam, Taskeen; Kaye, Tom (Journal of Learning for Development, 2020)
Since the onset of COVID-19, governments have launched technology-supported education interventions to ensure children learn. This paper offers a narrative synthesis of emerging evidence on technology-based education to understand the current experiences of learners, teachers and families. Studies find that few students in low- and middle-income countries have access to technology-supported learning with the most marginalised children appearing to have the least educational opportunities. As such, the education response to COVID-19 could widen existing inequalities.
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found